2007 IEEE Symposium on VLSI Circuits 2007
DOI: 10.1109/vlsic.2007.4342678
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated 1.2V-to-6V CMOS Charge-Pump for Electret Earphone

Abstract: To reduce the chip size and guarantee the reliability of This work proposes a new charge pump design that pumping capacitors, the Cockcroft-Walton-based multiplier achieves a high set-up ratio for electret earphone driving cell [2] with strong-inversion MOS capacitor is adopted. But circuits. The voltage pumping cell is based on due to the low system supply voltage, the effective value of Cockcroft-Walton topology to achieve small area with constant MOS capacitor decreases since it may be away from strong MOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Both [11,12] would be capable of providing the voltages necessary for programming FG transistors via hot-electron injection if no significant voltage overhead is required for the programming circuitry, and they both provide larger current-driving capabilities than the proposed charge pump. However, their ripple is larger, and they consume considerably larger real estate.…”
Section: Measurement Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both [11,12] would be capable of providing the voltages necessary for programming FG transistors via hot-electron injection if no significant voltage overhead is required for the programming circuitry, and they both provide larger current-driving capabilities than the proposed charge pump. However, their ripple is larger, and they consume considerably larger real estate.…”
Section: Measurement Resultsmentioning
confidence: 99%
“…The work in [10] showed that, for high-voltage charge pumps (e.g., V out > 2V dd ), the output ripple and efficiency of a charge pump can be improved by using complementary charge-pump structures, and simulated ripples of 65-73 mV were achieved. The charge pumps of [11,12] leveraged closed-loop structures to achieve ripple voltages in the tens-of-millivolts range; however, closed-loop operation does not guarantee low ripple voltages [13,14].…”
Section: Charge-pump Backgroundmentioning
confidence: 99%
“…In addition, the generator must also adjust V op to maintain a constant excess bias when the breakdown voltage changes, due to process and temperature variations and to account for current absorption variations at V op due to increase of brightness [3,4]. The charge pump proposed in [5] is insensitive to current variations but still the charge pump is sensitive to temperature fluctuation. Thus maintaining the excess bias irrespective of process, voltage, temperature, and brightness (PVT-B) variations is essential to ensure constant and reliable sensitivity levels of SPAD arrays over long periods of time, as demanded by today's applications.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, exploring a more effective control scheme [10] to reduce output ripple of switched-capacitor DC-DC converter with the variable output voltages for sub-threshold digital circuits is the focus of this paper. modulation (PDM) for feedback control [2]- [4], as shown in Fig. 2.…”
Section: Introductionmentioning
confidence: 99%